2001
DOI: 10.1097/00004872-200108000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, endothelial function and circulating endothelin concentrations in liver transplant recipients

Abstract: Our results show increased blood pressure with suppressed circadian blood pressure variability in liver graft recipients 6 weeks after transplant and no change in endothelial function and plasma endothelin concentrations. Therefore, the blood pressure increase documented in our study cannot be explained by endothelial dysfunction. Twenty-four hour ABPM should be performed routinely in patients who have undergone liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Although endothelial dysfunction is prevalent in renal and cardiac transplant recipients (14,22,(41)(42)(43)(44), the only previous report on FMD after OLT describes a 5% brachial artery dilatation after ischemia, which was similar to that of controls (17). In our study, controls FMD values were more in line with the usual values reported in healthy subjects (10%) and importantly, FMD was not impaired in the OLT patients.…”
Section: Endothelial Function After Oltsupporting
confidence: 82%
See 1 more Smart Citation
“…Although endothelial dysfunction is prevalent in renal and cardiac transplant recipients (14,22,(41)(42)(43)(44), the only previous report on FMD after OLT describes a 5% brachial artery dilatation after ischemia, which was similar to that of controls (17). In our study, controls FMD values were more in line with the usual values reported in healthy subjects (10%) and importantly, FMD was not impaired in the OLT patients.…”
Section: Endothelial Function After Oltsupporting
confidence: 82%
“…After organ transplantation, an impaired balance between vasodilatory and vasoconstrictive mediators has been reported, with decreased endothelial NO bioavailability, enhanced sensitivity to ET-1 and significantly impaired FMD (8)(9)(10)(11)(12)(13)(14)(15). Few data are available concerning endothelial function after OLT (16,17), but cardiovascular complications are more prevalent in liver transplant recipients than in the general population (18). Among other etiologies, the use of calcineurin inhibitors (CNI) such as tacrolimus (TAC) has been cited as a cause of altered endothelial function (19,20).…”
Section: Oliviermentioning
confidence: 99%
“…[21] found impaired endothelial‐dependent vasodilatation with skin laser‐doppler in heart transplant recipients and Passauer et al [20] found impaired response to Ach in renal transplant recipients investigated by venous occlusion plethysmography. However, Cifkova et al [22] could not detect any signs of impaired endothelial‐dependent vasodilatation despite elevated blood pressure in a longitudinal study before and after liver transplantation. The diverging results in the different studies may thus be explained by higher incidence of pretransplant vascular dysfunction in heart and renal transplant recipients than in lung and liver recipients [2,5,23].…”
Section: Discussionmentioning
confidence: 99%
“…ABPM plays a role in hypertension diagnosis in LT recipients; in one study of 15 patients, only 40% of recipients were found to be hypertensive by office BP measures. Over six wk post‐LT, mean 24‐h SBP increased from 118 to 140 mmHg, and DBP from 86 to 104 mmHg (61). In another study, it was found that the dose of prednisone was inversely correlated with the magnitude of nocturnal BP dipping (13).…”
Section: Abpm In Liver and Small Bowel Transplantationmentioning
confidence: 99%
“…While end‐stage liver disease (ESLD) patients had similar circadian BP profiles as normotensive controls before transplantation; LT recipients receiving cyclosporine or tacrolimus had elevated nocturnal BP compared with both control subjects and patients with pre‐transplant ESLD (63). The BP increase in LT recipients may not be explained by endothelial dysfunction (61), despite the observation that nocturnal non‐dipping is related to proteinuria, at least in pediatric LT recipients (64).…”
Section: Abpm In Liver and Small Bowel Transplantationmentioning
confidence: 99%